Pembiayaan Syariah dan Stabilitas Makroekonomi: Implikasi terhadap Perkembangan UMKM di Indonesia - Sunaryono, Sunaryono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) IBE Indonesia, 2024)
This research examines the relationship between Sharia financing, macroeconomic stability represented by BI Rate and inflation, and the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Secondary data from official sources such as Bank Indonesia, the Central Statistics Agency, and the Financial Services Authority were used to analyze a time period from 2003 to 2022. The research findings, using the Autoregressive Distributed Lag (ARDL) analysis method, indicate that Sharia financing has a significant long-term impact on MSME growth, while macroeconomic stability, particularly inflation, also has a substantial long-term influence on MSME development. The implications of these findings underscore the importance of policies supporting the development of Sharia financing and maintaining macroeconomic stability to foster sustainable long-term growth for MSMEs in Indonesia